Ask a New Question
Search
Multiply the following two binomials.
1. (6x - 1)
2. (-3x + 1)
1 answer
(6x - 1)(-3x + 1)
= 6x(-3x) + 6x(1) - 1(-3x) - 1(1)
= -18x^2 + 6x + 3x - 1
= -18x^2 + 9x - 1
Ask a New Question
or
answer this question
.
Similar Questions
Multiply the binomials: (x – 9)(x + 2).
(1 point) Responses x2 – 7x – 18 x 2 – 7 x – 18 x2 – 11x – 18 x 2 – 11 x
11 answers
Which of the following should be done to both sides of the equation x12=6 to solve the value of x ?(1 point) Responses multiply
1 answer
Which of the following should be done to both sides of the equation x12=6 to solve the value of x ?(1 point)
Responses multiply
1 answer
Which of the following should be done to both sides of the equation x12=6 to solve the value of x ?(1 point) Responses multiply
1 answer
more similar questions